WIN-WIN SOLUTION DALAM KONFLIK PUSAT-DAERAH: PENDEKATAN UTILITARIAN - Setiaji, Bambang (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2000)
This article is to provide a theoretical analysis of the problem faced by the central government, i.e., a want of some regions to choose the wider autonomy or independence. In the utilitarian approach, the concepts of choosing between autonomy and independence, or centralized are described as a trade off. Then the territory/the point of harmony between the central and regions will occur if only the central - the regions are combined making a synergy, and both are better off, compared with the separation between them.For an empirical analysis, this model describes a process of the bargaining between the central and the regions (bargain behavior model) that each of the party is to improve utility.